2013
DOI: 10.1121/1.4832915
|View full text |Cite
|
Sign up to set email alerts
|

Contour identification with pitch and loudness cues using cochlear implants

Abstract: Different from speech, pitch and loudness cues may or may not co-vary in music. Cochlear implant (CI) users with poor pitch perception may use loudness contour cues more than normal-hearing (NH) listeners. Contour identification was tested in CI users and NH listeners; the five-note contours contained either pitch cues alone, loudness cues alone, or both. Results showed that NH listeners' contour identification was better with pitch cues than with loudness cues; CI users performed similarly with either cues. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Also, because of the coarse spectral and temporal resolution of the artificial electric stimulation, pitch discrimination in CI users is relatively poor, and it is reasonable to assume that CI users may place greater weight on loudness cues during contour perception tasks than NH listeners. This has been supported by several previous CI studies, both for musical melodies [6,11] and Mandarin tone contours [8,12] using either explicit loudness contour manipulation [6,8] or implicit manipulation of loudness-related acoustic cues [11,12]. Here we build on these studies and examine the weighting of loudness contour and pitch contour cues by Mandarin-speaking CI users on in lexical tone perception.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Also, because of the coarse spectral and temporal resolution of the artificial electric stimulation, pitch discrimination in CI users is relatively poor, and it is reasonable to assume that CI users may place greater weight on loudness cues during contour perception tasks than NH listeners. This has been supported by several previous CI studies, both for musical melodies [6,11] and Mandarin tone contours [8,12] using either explicit loudness contour manipulation [6,8] or implicit manipulation of loudness-related acoustic cues [11,12]. Here we build on these studies and examine the weighting of loudness contour and pitch contour cues by Mandarin-speaking CI users on in lexical tone perception.…”
Section: Introductionsupporting
confidence: 53%
“…However, pitch is not the only dimension along which the auditory brain can perceive variations from low to high. Loudness and timbre variation over time can also be perceived as contours [6,7]. Nevertheless, in NH listeners, loudness contours and timbre contours have much less influence than pitch variation on Mandarin tone or musical melody perception, as demonstrated in studies using constant-pitch [7], degradedpitch [8], whisper [9], or inharmonicity [10].…”
Section: Introductionmentioning
confidence: 99%
“…1 for examples). That is, temporal pitch cues may be degraded while place pitch cues may be enhanced with higher F0s (Singh et al, 2009;Luo et al, 2014). The data of individual CI users in Fig.…”
Section: A Basic Pitch Ranking and Melodic Interval Rankingmentioning
confidence: 97%
“…Previous studies have also suggested that melodic contours could be used as assessment stimuli for perceptual and cognitive dysfunctions. For example, a clinical application has been applied for cochlear implant (CI) problems ( Galvin et al, 2008 , 2009 ; Loui et al, 2008 ; Luo et al, 2014a , b ). The general findings were that contour recognition and timbre perception are key in dictating auditory impairment.…”
Section: Introductionmentioning
confidence: 99%
“…The instrumental timbre provides a perceptual cue to segregate and/or integrate multi-layered streams of music, while voice timbre plays the same role in conversation against other environmental noises and/or among a crowd ( Broadbent, 1958 ; Bregman, 1999 ). That is, one can employ diverse and subtle acoustic features, such as loudness, pitch, and timbre, to differentiate the target sound from the distracting sounds ( Allen et al, 2011 ; Best et al, 2011 ; Luo et al, 2014a , b ). Previous research ( Janata, 2005 ; Jeong and Lesiuk, 2011 ) has claimed that, when given in a polyphonic texture, the melodic CIT can mimic the nature of real-world auditory surroundings in which environmental sounds, speech and music are simultaneously heard.…”
Section: Introductionmentioning
confidence: 99%